Fortalecimiento muscular del miembro inferior post lesión en los pacientes de la clínica del deporte rehabilitación física y deportiva clinider en el periodo marzo a mayo 2011. - Robalino, Yadira (2011)
This research has as main objective to know the importance of implementing strength training before, during and after a lower limb injury as not only athletes but also in sedentary people because small increases in your muscles can make a big difference physical capacity, especially in people with low muscle mass and muscle strength. Strengthening exercises are important not only in people like athletes or sedentary patients already mentioned above but also for the elderly. Studies suggest that strength exercises also may help prevent osteoporosis. People with high muscle strength statistically live longer. In this study highlight, the strength training as an essential part in the physical therapy because it increases the performance capability, the muscles can better protect joints and reduce susceptibility to injury.